Management of sport injury using the concept of "do rice, don't harm" - Rosadi, Rakhmad; Wardojo, Sri Sunaringsih Ika (Journal of Community Service and Empowerment, 2022)
Increasing physical capacity or performance after injury to students is a procedure that is in accordance with the commitment to achieving the Sustainable Development Goals (SDGs) in the health sector. This service activity aims to increase the active participation of teachers and students in overcoming sports injury health problems. The approach method used in this service activity is to use a synergistic partnership improvement to increase the participation of partners. The approach was carried out with the school health unit (Unit Kesehatan Sekolah/UKS) officers and students. The implementation of this activity received positive support from the principal and sports teachers and is an activity that has never been done in this place. This activity is the result of collaboration between the Faculty of Health Sciences UMM and SMPN 26 Malang City. Based on the results of the evaluation of the training activities carried out, it was found that the participants were able to take part in this activity well and enthusiastically as indicated by an increase in knowledge of 75%. This means that there is an increase in the active participation of teachers and students in overcoming sports injury health problems.